24 h mortality and its predictors among road traffic accident victims in a resource limited setting; a multicenter cohort study - Kamabu, Kinyamaniyi; Soria, Jorge La O; Tumwesigye, Deus; Okedi, Xaviour Francis; Kyomukama, Lauben; Muhumuza, Joshua; Musinguzi, Brian; Kavuma, Daniel; Vivalya, Bives Mutume Nzanzu; Loduk, Michael; Abdullah, Wani Shabani (BMC surgery, 2023)
Introduction: The incidence of road traffic accidents (RTAs) is on the rise contributing to the global burden of mortality as a major global health threat. It has been estimated that 93% of RTAs and more than 90% of the resulting deaths occur in low and middle income countries. Though death due to RTAs has been occurring at an alarming rate, there is paucity of data relating to incidence and predictors of early mortality. This study was aimed at determining the 24 h mortality and its predictors among RTA patients attending selected hospitals in western Uganda. Methods: This was a prospective cohort that consecutively enrolled 211 RTA victims admitted and managed in emergency units of 6 hospitals in western Uganda. All patients who presented with a history of trauma were managed according to the advanced trauma life support protocol (ATLS). The outcome regarding death was documented at 24 h from injury. Data was analyzed using SPSS version 22 for windows. Results: Majority of the participants were male (85.8%) aged 15–45 years (76.3%). The most common road user category was motorcyclists (48.8%). The 24 h mortality was 14.69%. At multivariate analysis, it was observed that a motorcyclist was 5.917 times more likely to die compared to a pedestrian (P = 0.016). It was also observed that a patient with severe injury was 15.625 times more likely to die compared to one with a moderate injury (P < 0.001). Conclusion: The incidence of 24 h mortality among road traffic accident victims was high. Being motorcycle rider and severity of injury according to Kampala trauma score II predicted mortality. Motorcyclists should be reminded to be more careful while using the road. Trauma patients should be assessed for severity, and the findings used to guide management since severity predicted mortality.
Keywords: 24 h mortality; Road traffic accident; Low income country; Predictors